Impact of (Manna) for individual and society: An analytical study - Al- Anzy, Saida Rida Mrbid (Journal of Islamic Sciences, 2019)
The purpose of this research to explain the reality of (Manna) and the implications of the researcher used the analytical method based on the method of deductive and deductive in some cases and reach the most important results that semi- hypocrisy in a mosque that both invalidate the work، To the need to refer to the book and the Sunnah guidance of the righteous ancestor and derive guidance from them، especially with regard to social relations.